2018
DOI: 10.1590/1809-4430-eng.agric.v38n6p885-892/2018
|View full text |Cite
|
Sign up to set email alerts
|

Consumption, Efficiency and Water Content of Arugula Under Different Management of Brackish Nutritional Solutions

Abstract: The need to use strategies for using brackish water in agriculture, especially in semi-arid conditions, is evident. Based on this information, this study was developed with the aim of evaluating the consumption, efficiency and water content, as well as the dry mass of the arugula plants (cv. Broad Leaf) exposed to brackish nutrient solutions as a function of replacement strategies and circulation frequencies. The treatments consisted of six salinity levels of the nutrient solution (1.5, 3.0, 4.5, 6.0, 7.5 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
3
4
1
Order By: Relevance
“…These results differ from those observed by Campos Júnior et al (2018), who worked with strategies to replace the evapotranspired depth in arugula plants and found a linear decrease as the nutrient solution salinity increased, in the replacement with supply water and brackish water, with reductions of 0.0431 and 0.033 per unit increment of EC ns , respectively.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…These results differ from those observed by Campos Júnior et al (2018), who worked with strategies to replace the evapotranspired depth in arugula plants and found a linear decrease as the nutrient solution salinity increased, in the replacement with supply water and brackish water, with reductions of 0.0431 and 0.033 per unit increment of EC ns , respectively.…”
Section: Resultscontrasting
confidence: 99%
“…When NaCl, CaCl 2 and MgCl 2 were used, the reductions in the pH ns at 50 DAS were equal to 4.54, 7.93 and 9.67%, respectively. In general, the pH ns variations in this study did not exceed the range from 5.5 to 6.5 suggested by Silva et al (2018), which would cause problems in the absorption of nutrients.…”
Section: Resultssupporting
confidence: 45%
See 1 more Smart Citation
“…Minimization of matrix potential due to the absence of soil favors the absorption of water by plants, which becomes predominantly affected by the osmotic potential of nutrient solution (Santos Júnior et al, 2016;Campos Júnior et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have already shown the technical viability of using brackish water to prepare nutrient solutions for cultivating different plant species; for example, arugula (Campos Júnior et al, 2018), cauliflower (Cruz et al, 2018), lettuce (Soares et al, 2019), coriander (Silva et al, 2020b), chicory (Alves et al, 2019;Silva et al, 2020a), among others.…”
Section: Introductionmentioning
confidence: 99%